Oribatid mites (Acari, Oribatida) from riverine environments in New Caledonia - Sergey G. Ermilov; Nathalie J. Mary (Persian Journal of Acarology, 2025)
The present study is based on oribatid mite materials collected from benthic samples in four river locations on the Grande Terre Island, New Caledonia. A list of eight species, belonging to six genera and five families, is presented; among them are taxa that are new for the fauna of New Caledonia. One new species of the genus Trhypochthoniellus (Trhypochthoniidae)—T. grandensis sp. nov.— is described; it is mainly characterized by the nasiform rostrum having ridges; slightly polygonate ornamentation on the notogaster and in the anogenital region; the absence of the bothridial seta and bothridium; the relative length of prodorsal setae: in ˃ le ˃ ro; 14 pairs (p3 absent) of the notogastral setae setiform (except f1 as alveolus), nearly smooth; the relative length of the notogastral setae: c3, e2, h1, h2, p2 ˃ cp, e1, h3, p1 ˃ d2 ˃ c1, c2, d1, f2; six pairs of genital setae.